Estrategias financieras aplicadas al proceso de sostenibilidad y crecimiento de las pequeñas empresas comerciales de la ciudad de Loja - Calva Chamba, Jhulissa Lizbeth (2022)
This work was carried out with the main objective of "Analyzing the financial strategies applied to the growth and sustainable development of small companies in the city of Loja during the period 2019-2020." For the development of this study, different methods were used that were of great importance to find timely and real data, among them: the inductive, deductive, scientific method, the analytical and synthetic method, as well as appropriate techniques and tools such as the survey and interview which helped to carry out the diagnosis of the current strategies of small commercial companies, identify the influence of the external and internal environment in the growth process of said companies and finally in the preparation of the financial strategies manual for the development and sustainable growth of small business enterprises. Finally, as results, it was obtained that 69.57% of these companies use financial strategies, but these are not well established and do not consider the opinion of the collaborators in decision-making, which is causing a waste of economic resources and human, and also does not perform an analysis of all external and internal factors in the growth and sustainable development of small business enterprises; since generally the owners focus on other aspects such as customer service; forgetting to carry out information review processes and application of financial indicators to show the real situation of the companies.